Effect of thermo-oxidative aging on mechanical and morphological properties of bagasse filled polypropylene composites - Suryadiansyah, Dr. Ir.; Muhd Arif, Mat Saad (Universiti Sains Malaysia (USM), 2011)
Organized by Universiti Sains Malaysia (USM), 26th - 27th November 2008 at Naza Hotel, Penang, Malaysia.